Metacognitive therapy (MCT+) in patients with psychosis not receiving antipsychotic medication: A case study - Balzan, Ryan P.; Galletly, Cherrie (Frontiers in Psychology, 2015)
Background: Psychotherapies for psychosis typically aim to develop an awareness of the implausible content of a delusion or target the underlying cognitive biases (i.e., problematic thinking styles, such as hasty decisions and illusory control) that foster and maintain delusional beliefs. A recently designed individual-based treatment entitled metacognitive therapy (MCT+) combines these two approaches. Emerging evidence suggests individualised MCT+, when used concurrently with antipsychotic medication, may be an effective psychological treatment for reducing delusional symptoms. However, it remains to be tested whether MCT+ can be effective in patients with active delusions who are not currently receiving psychotropic drugs. Method: We present two cases (one patient with schizophrenia and the other with delusional disorder) experiencing active delusions who underwent four-weeks of intensive MCT+, without concurrent antipsychotic medication (minimum 6-months unmedicated). Baseline and 6-week follow-up data are presented on a variety of measures assessing delusion symptom severity (i.e., PANSS, PSYRATS, SAPS), clinical insight, and cognitive bias propensity. Results: After 4-weeks of MCT+, both patients showed substantial reduction in delusional symptoms, reported improved clinical insight, and were less prone to making illusory correlations. Conclusions: The presented case studies provide preliminary evidence for the feasibility of MCT+ in treating patients not taking, or resistant to, antipsychotic medication.